Switchable acoustic projection displays based on coding composite structures - Han, Jianning; Wang, Rui (Frontiers in Physics, 2023)
Projection display is of relevance for various applications, for example information communication, encryption and storage. Although numerous optical projection devices have been reported in past years, the realization of switchable acoustic projection display without built-in circuits is a challenge. In this work, we propose a coding composite structure composed of a perforated plate and a coiling-up cavity with six interdigital rigid walls to achieve switchable acoustic projection displays. The configuration can be served as bits ‘0’ and ‘1’ by using forward and backward placements, respectively. The required projection can be displayed as long as the expected image regions are filled with bit ‘1’ and other regions are filled with bit ‘0’. By switching control wave Pc, the projected image is able to be switched from ‘Off state’ to ‘On state’ accordingly. The underlying physical mechanism is the different scattering responses between two coding bits induced by coherent superposition. Our design provides an effective solution for the construction of acoustic projection displays with switchable feature, which may have potential applications in information encryption and storage.